CSR reporting by Chinese and Western MNEs: Patterns combining formal homogenization and substantive differences - Irina Ervits (International Journal of Corporate Social Responsibility (JCSR), 2021)
In light of the growing economic might and intensification of global activities of Chinese multinational enterprises (MNE), this paper looks into the nature of their corporate social responsibility (CSR) reporting. CSR communications of the largest Chinese companies and their counterparts from advanced economies have been compared based on quantitative and qualitative content analysis of CSR reports. A mixed method approach has been rarely utilized in the analysis of CSR reporting. To analyze CSR reports the paper uses a two-dimensional conceptual framework based on Wood (Acad Manag Rev 16:691-717, 1991); Jamali and Mirshak (J Bus Ethics 72:243-262, 2007) and Lockett, Moon and Visser (J Manag Stud 43:115-136, 2006); Moon and Shen (J Bus Ethics 94:613-629, 2010). The findings indicate that quantitatively Chinese MNEs display patterns of CSR reporting comparable to major MNEs in developed economies. This paper argues that just like MNEs from developed economies Chinese MNEs use a global CSR reporting template as a convenient tool to align and harmonize various isomorphic pressures. However, qualitatively substantive discrepancies in content have been also identified due to national or other contextual characteristics. The analysis reveals a complex picture of national and international isomorphic forces at play. The paper addresses the lack of consensus concerning convergence/divergence of CSR reporting across the globe and, more specifically, between developed economies and emerging markets. In this respect this paper responds to the general call for research looking into various aspects of business operations, including CSR reporting, of MNEs from emerging markets.
Keywords: 650; MNEs; CSR reporting; Emerging markets; Homogenization; Isomorphism; China